2008
DOI: 10.1038/modpathol.3801002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of thyroid transcription factors Pax8 and TTF-2 (FoxE1) in thyroid epithelial neoplasms

Abstract: Thyroid-specific transcription factors, Pax8, TTF-1, and TTF-2, are crucial for thyroid organogenesis and differentiation. Compared with TTF-1, the other two markers have scarcely been investigated in surgical pathology. The goal of this study is to evaluate the expressions of these markers in thyroid tumors of the full spectrum of differentiation, with special emphasis on anaplastic carcinomas. A total of 94 cases of thyroid neoplasms were studied: 17 papillary carcinomas, 18 follicular adenomas, 16 follicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
174
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(200 citation statements)
references
References 40 publications
16
174
3
Order By: Relevance
“…Another type of carcinoma with which pleomorphic mesotheliomas can potentially be confused is anaplastic thyroid carcinoma, as these tumors frequently metastasize to the lung and may involve the pleura. As in the case of pleomorphic carcinomas of the lung, anaplastic thyroid carcinomas do not express calretinin, mesothelin or WT1, but can express Pax8, 23,24 a marker that is absent in mesotheliomas. 25 TTF-1 has little value as it has been reported to be expressed only in a small percentage of anaplastic thyroid carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another type of carcinoma with which pleomorphic mesotheliomas can potentially be confused is anaplastic thyroid carcinoma, as these tumors frequently metastasize to the lung and may involve the pleura. As in the case of pleomorphic carcinomas of the lung, anaplastic thyroid carcinomas do not express calretinin, mesothelin or WT1, but can express Pax8, 23,24 a marker that is absent in mesotheliomas. 25 TTF-1 has little value as it has been reported to be expressed only in a small percentage of anaplastic thyroid carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…25 TTF-1 has little value as it has been reported to be expressed only in a small percentage of anaplastic thyroid carcinomas. 23,26 Pleomorphic mesotheliomas can also be confused with some sarcomas. The two sarcomas with the greatest potential of being confused with pleomorphic mesotheliomas are angiosarcomas and the pleomorphic variant of malignant fibrous histiocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…It may also mediate neoplastic transformation as 15 PAX 8-PPARg rearrangement occurs in 20-30% of follicular thyroid carcinomas. [12][13][14][15] PAX 8, together with PAX 2 and PAX 5, controls lymphoid genesis, especially the maturation of B cells. 26 …”
Section: Pax 8 In Embryogenesismentioning
confidence: 99%
“…A few limited studies have identified PAX 8 in neoplasms of the organs the embryogenesis of which is under control of this transcription factor, including thyroid follicular neoplasm, [12][13][14][15] renal cell carcinoma, 11,16 nephrogenic adenoma, 17 and ovarian carcinoma. [18][19][20] Confirmation of PAX 8 as a sensitive marker for these tumor types is required.…”
mentioning
confidence: 99%
“…[14][15][16] Although PAX8 has been most studied in renal tissues and neoplasms, 17 it has been recently recognized as a useful marker in distinguishing ovarian from breast carcinoma, 18 and as a marker of thyroid epithelial neoplasms. 19 Moreover, our group recently observed intense PAX8 reactivity in pancreatic neuroendocrine tumors and normal pancreatic islets in a large tissue microarray evaluation of PAX8 immunoreactivity of non-renal tissues/neoplasms. 20 Very little is known about the role of PAX8 in endocrine cell development, and differential PAX8 expression in neuroendocrine tumors of the pancreas, gastrointestinal tract, and lung could be of potential clinical utility.…”
mentioning
confidence: 97%